(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Poverty is intrinsically linked to sustainable development. Seventy percent of India lives in village, most of whom derive their total sustenance from agriculture or a related activity. Their security is synonymous with agriculture security, food security and farmer’s security. Agrarian crisis since the 1990s has been one of the major problems India is facing, driving hordes of farmers to suicide. Seed, agrochemicals, water, power, soil health, agricultural practices, remunerative prices, erosion of agro-biodiversity, post-harvest technologies, augmentation of income through other sources, education, affordable healthcare, accessibility to loans, transportation, and infrastructure, are some of the factors that impact rural security. With all the resources In dia has, whether natural or man-made, it has the means to eradicate poverty, but do those who govern, have the will?